Self-Reported Mental Health of Nurses at Dr. M.M. Dunda Hospital, Gorontalo Regency - Suleman, Ibrahim; Zainuddin; Antu, Mihrawaty S; Aswad, Yusrin (International Journal of Public Health Excellence (IJPHE), 2024)
Mental Health is a condition where an individual can develop physically, mentally, spiritually and socially so that the individual is aware of his or her own abilities, can handle pressure, can work productively, and is able to contribute to his or her community. Several factors cause mental disorders, namely a work environment with a high risk of violence, facing various types of stress and an uncomfortable workplace. Mental disorders can take the form of changes in the mental and emotional atmosphere which have an impact on physical disorders and are rarely recognized by sufferers, including nurses. Nursing is a profession that has a very high risk of stress, because nurses have very high duties and responsibilities for the safety of human life. The aim of the research is to determine the self-reporting of mental health of nurses at RSUD Dr. M.M Dunda Limboto, Gorontalo Regency. The research design is a descriptive design, with a sampling technique using non-probability sampling, namely snowball sampling. The sample in this study using the Slovin formula obtained 175 respondents. The results of this research showed that 131 respondents (74.9%) were not indicated, and 44 respondents were indicated (25.1%). The conclusion of this study shows that the majority of nurses at RSUD M.M. Dunda Limboto has no indication of a mental health disorder which is known from the Self Reporting Questionnaire assessment. It is hoped that nurses can maintain mental health by doing self-rewards to increase their capacity as nurses.